Prescribed Walking for Glycemic Control and Symptom Management in Patients Without Diabetes Undergoing Chemotherapy. Issue 1 (January 2021) - Hammer, Marilyn J.; Eckardt, Patricia; Cartwright, Frances; Miaskowski, Christine
Abstract : Background: Hyperglycemia may potentiate symptom experiences. Exercise is a nonpharmacological intervention that can potentially improve glycemic control and mitigate symptom experiences in patients undergoing chemotherapy for cancer. Objectives: The primary objective was to assess the feasibility of patients engaging in a walking exercise study for 6 months. We also evaluated the effects of a prescribed walking program on glycemic control and for changes over time in the severity of pain, fatigue, depression, and sleep disturbance in patients undergoing chemotherapy for breast, lung, gynecologic, or gastrointestinal cancer. Methods: A randomized pilot intervention study was conducted to evaluate differences within and between a prescribed walking program intervention group and a control group. All patients were followed for 6 months, had glycosylated hemoglobin A1c measured at enrollment and 6 months, and completed symptom questionnaires at enrollment, 3 months, and 6 months. Data were analyzed using descriptive statistics and analysis of covariance. Results: Most of the patients who enrolled completed the 6-month study. The few who withdrew expressed feeling overwhelmed. The sample was predominately non-Hispanic White female patients with breast cancer with a normal-to-slightly-overweight body mass index. The intervention group had a slight decrease in glycosylated hemoglobin A1c at 6 months. In addition, at 6 months, compared to the control group, the intervention group had significantly less sleep disturbance and depression. No other within- or between-group differences were found. Discussion: It is feasible for patients undergoing chemotherapy to participate in a prescribed walking program. Exercise, such as walking, may decrease hyperglycemia and symptom severity. Additional research with larger samples is warranted. Abstract : Supplemental digital content is available in the text.